Association of Clinical and Economic Outcomes With Permanent Pacemaker Implantation After Transcatheter Aortic Valve Replacement - Aljabbary, Talal; Qiu, Feng; Masih, Shannon; Fang, Jiming; Elbaz-Greener, Gabby; Austin, Peter C.; Rodés-Cabau, Josep; Ko, Dennis T.; Singh, Sheldon; Wijeysundera, Harindra C. (JAMA network open, 2018)
The literature is inconsistent regarding the impact of permanent pacemaker implantation after transcatheter aortic valve replacement. To evaluate clinical and economic outcomes in patients who required permanent pacemaker implantation during the index hospitalization after transcatheter aortic valve replacement. This retrospective, population-based cohort study using data from a multicenter registry included patients who underwent a transcatheter aortic valve replacement procedure from April 1, 2010, to March 31, 2015, in Ontario, Canada, with follow-up to March 31, 2017. Patients who had a previously implanted permanent pacemaker or who died during the index hospitalization were excluded. Inverse probability of treatment weighting using the propensity score was used to adjust for baseline differences between the pacemaker and nonpacemaker groups. Patients received a permanent pacemaker during the index hospitalization after transcatheter aortic valve replacement. All-cause mortality, readmission, readmission for heart failure, emergency department visits, and cumulative 1-year health care costs. The study cohort consisted of 1263 patients (mean [SD] age, 82.3 [7.2] years; 595 [47.1%] female; 137 [10.8%] rural), of whom 186 (14.7%) required permanent pacemaker insertion during the index hospitalization after transcatheter aortic valve replacement. Mean follow-up was 990 days. After propensity score weighting, over the entire follow-up period, pacemaker implantation was associated with significantly higher all-cause mortality (43.9% vs 31.7%; hazard ratio [HR], 1.40; 95% CI, 1.01-1.94; P = .04), all-cause readmission (80.9% vs 70.6%; HR, 1.28; 95% CI, 1.15-1.43; P < .001), and emergency department visits (95.5% vs 87.3%; HR, 1.28; 95% CI, 1.08-1.52; P = .004). Pacemaker implantation was also associated with significantly greater readmission for heart failure (33.9% vs 19.1%; HR, 1.90; 95% CI, 1.53-2.36; P < .001). There were no statistically significant differences between groups in adjusted cumulative health care costs 1 year after discharge. New permanent pacemaker implantation after transcatheter aortic valve replacement was associated with significantly greater morbidity and mortality at long-term follow-up. However, this did not translate to a difference in cumulative health care costs after hospital discharge.